National Movement Resistance against Adahir Barbaryduring Colonialism - طبيش, عبد الكريم (Milev Journal of Research and Studies, 2020)
During modern era of Algerian history occurred events which affected the destiny of Algeria both in civilian and political plans. The emergence of ” Dahir Barbary “is of these events which had a great importance and got priority to political and military French leaders during Algeria ‘s occupation. But, Algerian national movement of reform faced this danger by publishing many books, revues in order to prevent from its danger. This study aims to answer to many questions including the meaning of Dahir Barbary, the domains where Algerian national movement intervened and asking about success in its task.